Intensity squeezed light from a single emitter - Götzinger, Stephan; Chu, Xiao Liu; Sandoghdar, Vahid (Optics InfoBase Conference Papers, 2017)
We demonstrate a sub-shot noise single-emitter quantum light source, which uses a metallo-dielectric antenna for near-unity photon collection to obtain the most regular stream of single photons reported to date.
CRIS-Team Scopus Importer:2023-03-27